PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PT. UNITED TRACTORS, TBK CABANG JAKARTA CAKUNG - Angga Eka Prastyo; Donny Dharmawan (Jurnal Ekonomi dan Industri, 2023)
This research aims to analyze the influence of "The Influence of Motivation and Organizational Culture on Employee Job Satisfaction at PT. United Tractors, Tbk Jakarta Cakung Branch. This research is included in the category of causal associative research using a quantitative approach. The research method used simultaneous linear regression analysis. Based on the results of data analysis simultaneously there is a significant influence of motivation and organizational culture on PT employee job satisfaction. United Tractors, Tbk Jakarta Cakung Branch